1993
DOI: 10.1254/jjp.61.367
|View full text |Cite
|
Sign up to set email alerts
|

Improving Effects of FG-7080, a Serotonin Reuptake Inhibitor, on Scopolamine-Induced Performance Deficits of Memory Tasks in Rats

Abstract: Effect of an extract of Ginkgo biloba leaves (EGb) on oxidative metabolism was studied using rat brain neurons and 2',7'-dichlorofluorescin fluorescence. lonomycin (100 nM to 1 ƒÊM), a Ca2+-iono phore, dose-dependently augmented the 2',7'-dichlorofluorescin fluorescence in the presence of external Ca2+, but not under the external Ca2+-free condition. Preincubation of neurons with EGb (3 ƒÊg/ml) greatly reduced the ionomycin-induced increase in 2',7'-dichlorofluorescin fluorescence. Results suggest that EGb may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…Ionomycin also augmented the intensity of DCF fluorescence significantly as shown previously (1,13). However, the potency of ionomycin in augmenting DCF fluorescence (the potency of oxidative effect of ionomycin) was unknown.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Ionomycin also augmented the intensity of DCF fluorescence significantly as shown previously (1,13). However, the potency of ionomycin in augmenting DCF fluorescence (the potency of oxidative effect of ionomycin) was unknown.…”
supporting
confidence: 72%
“…In fact, ionomycin that greatly increases the [Ca 2+]; of neurons augmented DCF fluorescence (Fig. 3A), suggesting an oxidation of cellular DCFH, depending on the [Ca 2+], increased by ionomycin (1). The potency of ionomycin in increasing the intensity of DCF fluorescence was almost equivalent to that of hydrogen peroxide at concentrations of 100-300 pM (Fig.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…We have shown that EGBL protects neurons suffering from oxidative stress induced by hydrogen peroxide 7) and decreases oxidative metabolism in resting and Ca 2ϩ -loaded neurons. 12,16) Oxidative stress is also induced by abnormally increasing [Ca 2ϩ ]i in neurons. 20,21) Therefore, if EGBL prevents increasing [Ca 2ϩ ]i of neurons by excessive activation of glutamate receptor, it would contribute to the neuroprotective action of EGBL.…”
Section: Discussionmentioning
confidence: 99%
“…9,10) The extract exerts protective action (or antioxidant action) on neurons suffering from oxidative stress induced by hydrogen peroxide, one of ROS, and by overload of intracellular Ca 2ϩ . 7,11,12) EGBL and its constituents inhibit the response mediated by activation of NMDA receptor. 13,14) However, there is limited information concerning the effect of EGBL on response induced by activation of non-NMDA glutamate receptor.…”
Section: )mentioning
confidence: 99%